Formalization of domain problems described in the cause-and-effect diagram in the context of the software development process (2020)
The system analyst is responsible— in the early requirements elicitation process—for identifying the problems to be solved with a software application. Such identification is based on: (i) the analyst experience and knowledge about the domain area; and (ii) the stakeholder support. Problems are collected by the system analyst during the domain analysis for using them as the main input of the requirements specification. Such specification is consistent with the problems identified and the stakeholder needs. The system analyst detects and describes problems from the domain discourse recognition and eventually presents them in a formal way by using a representation diagram.